A Study on the MSMEs Growth of Cemilan Lepak and 30°C at POLBENG Business Expo Chapter II - Endah Laillatul Mirandha; M. Alkadri Perdana (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Polbeng Business Expo Chapter II is an event organized by International Business Administration students of the Class of 2022 as a practical application of business theories learned in lectures. The event aims to enhance students’ entrepreneurial and business management skills while supporting the development of local MSMEs. This final project involved 133 participants showcasing various products and services, mainly in the food and beverage sector, to create a competitive business environment. The activities included planning and budgeting, securing sponsors and participants, coordination with supervisors and the community, as well as exhibitions, competitions, and digital promotions. The results of the analysis show that the public's perception of Polbeng Business Expo Chapter II is in the high category, with 89.1% of respondents having a high perception, 5.9% having a moderate perception, and 4.9% having a low perception. Through this project, students faced real business challenges and successfully improved their practical skills in project management, marketing, negotiation, financial management, and digital promotion.